Synthesis, Mycobacterium tuberculosis H37Rv inhibitory activity, and molecular docking study of pyrazinamide analogs - Muhammad Zulqurnain, Nur Pasca Aijijiyah, First A. Wati, Arif Fadlan, Azminah Azminah, Mardi Santoso (Journal of Applied Pharmaceutical Science, 2023)
Pyrazinamide analogs 5a–h have been successfully synthesized by the Yamaguchi esterification method with yields ranging from 6% to 86%. Among pyrazinamides 5a–h, pyrazinamides 5d,g showed the best antituberculosis activity with MIC values
Keywords: Pyrazine-2-carboxamides, yamaguchi reaction, 2-4-6-trichlorobenzoyl chloride, antitubercular